2020
DOI: 10.3390/environments7060042
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production from Food Residues—The Role of Trace Metals and Co-Digestion with Primary Sludge

Abstract: The majority of municipal Wastewater Treatment Plants (WWTPs) in Sweden produce biogas from sewage sludge. In order to increase the methane production, co-digestion of internal sludge with Organic Fraction of Municipal Solid Waste (OFMSW) might be feasible in the future. The objective of this study was therefore to find a beneficial solution for the utilization of OFMSW at the WWTP in Varberg, Sweden. The effects of co-digesting primary sludge (PS) and OFMSW collected in the municipality, in different mixing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Finally, technological barriers rely on to lacking proven technologies to implement CE. In fact, most of companies still have limited circular designs [11], lack ability to deliver high quality manufactured products with circular process [9] or to find a beneficial solution for the utilization of material residues [13]. In addition, there are too few large-scale demonstration projects and lack of data on CE impacts [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, technological barriers rely on to lacking proven technologies to implement CE. In fact, most of companies still have limited circular designs [11], lack ability to deliver high quality manufactured products with circular process [9] or to find a beneficial solution for the utilization of material residues [13]. In addition, there are too few large-scale demonstration projects and lack of data on CE impacts [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an unusable product must be recycled as much as possible and energy must be obtained from the disposal of non-recyclable parts, by creating new synergies with the supply chain of the same and other products (e.g. Habagil et al, 2020 ; Yuan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…They reported significant improvements in volatile solid removal when the content of vegetable wastes in the mixture was increased and also when the feed's solid content was lowered. Similarly, Habagil et al [35] reported variations in biogas yields based on the organic load applied to the reactor and the C/N ratio, which was changed by altering the mixture proportion of food wastes and primary sludge. However, trying to set a specific C/N ratio for industrial digesters in an attempt to extrapolate results is not always easy.…”
Section: The Effect Of Organic Loading On Digestion Performancementioning
confidence: 96%